The influence of market orientation and enterpreneur orientation on competitive advantage Sweettooth Cake and Coffee Padang mediated by innovation product. - Ikhsan Rynaldo; Yunita Engriani (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze the influence of market orientation and entrepreneur orientation in building competitive advantage mediated by product innovation at Sweettooth Cake and Coffee Padang. The results of the study are (1) Market orientation has a positive and significant effect on the competitive advantage of Swettooth cake & Coffee. (2) Entrepreneurial orientation has a positive and significant impact on the competitive advantage of Swettooth cake & Coffee. (3) Marketorientation hasaa positive and significant impact on Swettooth cake & Coffee product innovation. (4) Entrepreneurial orientation hasapositive and significant impacton Swettooth cake & Coffee productinnovation. (5) Product innovation hasa positive and significantimpact on the competitive advantage of Swettooth cake & Coffee. (6) Market orientation has a positive and significant impact on the competitive advantage of Swettooth cake & Coffee through product innovation as a mediator. (7) Entrepreneurial orientation has a positive and significant impact on Swettooth cake & Coffee's competitive advantage through product innovation as a mediating variable.